Comic media in improving dental health knowledge in elementary schools - Indah, Amelia Algita; Tauchid, Siti Nurbayani (Journal Center of Excellent : Health Assistive Technology, 2025)
Background: Increasing knowledge and awareness of the importance of maintaining oral health is done by counseling, one of the counseling media that can be used to attract responden attention is in the form of images, one of which is comics. Objective: To analyze the level of knowledge of oral health before and after counseling with comic media for class 5th respondents of SDN Jampang Hambulu Bogor. Method: This type of research is a pre-experimental with a pretest and posttest with one group design, with a purposive sampling technique of 34 respondents of class 5th SDN Jampang Hambulu, the instruments used was a questionnaire sheets and comics. Results: The results showed that the average value of knowledge before counseling was 7 in the moderate category, and after counseling was 9,29 good category. The frequency distribution of the good category was 35,3% to 85,3%, the sufficient category was 52,9% to 14,7%, and the less category was 11,8% to 0%. Conclusion: Counseling with comic media effectively increases knowledge of oral health in class 5th respondets of SDN Jampang Hambulu.